New applications of pHluorin--measuring intracellular pH of prototrophic yeasts and determining changes in the buffering capacity of strains with affected potassium homeostasis - Maresová, Lydie; Hosková, Barbora; Urbánková, Eva; Chaloupka, Roman; Sychrová, Hana (Yeast, 2010)
pHluorin is a pH-sensitive variant of green fluorescent protein for measuring intracellular pH (pH(in)) in living cells. We constructed a new pHluorin plasmid with the dominant selection marker KanMX. This plasmid allows pH measurements in cells without auxotrophic mutations and/or grown in chemically indefinite media. We observed differing values of pH(in) for three prototrophic wild-types. The new construct was also used to determine the pH(in) in strains differing in the activity of the plasma membrane Pma1 H(+)-ATPase and the influence of glucose on pH(in). We describe in detail pHluorin measurements performed in a microplate reader, which require much less hands-on time and much lower cell culture volumes compared to standard cuvettes measurements. We also utilized pHluorin in a new method of measuring the buffering capacity of yeast cell cytosol in vivo, shown to be ca. 52 mM/pH for wild-type yeast and moderately decreased in mutants with affected potassium transport.
Keywords: homeostáza; draslík; Green Fluorescent Proteins; Saccharomyces cerevisiae Proteins; Hydrogen-Ion Concentration; Potassium; druhová specificita; Saccharomyces cerevisiae; Homeostasis; Buffers; Species Specificity; zelené fluorescenční proteiny; plazmidy; cytosol; Cytosol; Plasmids; pufry; buněčná membrána; Saccharomyces cerevisiae - proteiny; koncentrace vodíkových iontů; Cell Membrane